Bio-inspired approach for innovative design of knee protectors for recrceational sports - Ana Zdravkova; Ile Mircheski; Sofija Sidorenko (FME Transaction journal, 2020)
In this paper the process of an innovative design of a knee protector is presented. The main goal of the research was to find a creative design solution for more efficient protective equipment for light recreational sports. The research is based on an interdisciplinary approach where the possibilities of ergonomics and bionics methods were applied. In order to recognize and provide proper design requirements a valuable market research in the field of knee protector products was performed. An ergonomic research was implemented with intention to define the detailed requirements for more comfort, better functioning and better protection from injuries. The design process was completed following the problem driven bio-inspiration approach. The armadillo's shell structure, consisted of tiles connected with collagen fibers, was an inspiration for an innovative design approach. The result is a virtual 3D model of an innovative design of a knee protector, with intention to be further developed and tested as a 3D printed prototype, until achieving the phase of final product.
Keywords: Armadillo, Bionics, Ergonomics, Industrial Design, Knee protector